180k views
5 votes
2p +5q = 21
3p-2q=-16

2 Answers

3 votes

Answer:

q = 5

p = -2

Explanation:

I'm gonna use elimination

2p + 5q = 21 Multiply 3 ------> 6p +15q = 63

3p - 2q = -16 Multiply 2 -------> 6p -4q = -32

6p +15q = 63

6p -4q = -32 -__________

19q = 95

q = 5

To find P use any of the equations and substitute q to 5

3p -2(5) = -16

3p -10 = -16

3p = -6

p = -2

User SanketS
by
5.5k points
7 votes

Answer:

p =− 2

q = 5

Explanation:

Solve for the first variable in one of the equations, then substitute the result into the other equation.

p =− 2

q = 5

User Duncan Ogle
by
5.4k points